Improved Channel Estimation for DVB-T2 Systems by Utilizing Side Information on OFDM Sparse Channel Estimation - S. Ghazi-Maghrebi; S.H. Hashemi-Rafsanjani (AUT Journal of Electrical Engineering)
The second generation of digital video broadcasting (DVB-T2) standard utilizes orthogonal frequency division multiplexing (OFDM) system to reduce and to compensate the channel effects by utilizing its estimation. Since wireless channels are inherently sparse, it is possible to utilize sparse representation (SR) methods to estimate the channel. In addition to sparsity feature of the channel, there is usually some additional information, known as side information. The side information, in general application, is not used in ordinary sparse channel estimation methods. However, utilizing the side information may help improve the channel estimation. In this paper, we utilize side information to estimate sparse channel of an OFDM system. Also, for more verification of the proposed method in this paper, we have shown the impact of side information in the estimation procedure for an applied system such as DVB-T2 system. Simulation results, in this research, show that utilizing side information not only increases the performance of the DVB-T2 system, but also releases a portion of resources of the system such as estimation-pilots. It is obvious that these resources can be used for increasing data rate.